EFEKTIVITAS PENYELESAIAN DAN PENERIMAAN ATAS HASIL PEMERIKSAAN PAJAK PENGHASILAN ORANG PRIBADI (STUDI KASUS KPP PRATAMA MANADO) - Sumampouw, Fino Indra; Elim, Inggriani; Wokas, Heince (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Tax audit is a series of activities to search for, collect, and process data or other information to verify compliance fulfillment of tax obligations and for other purposes in order to implement the provisions of the tax legislation. It is also against the background of the tax laws in Indonesia in implementing tax collection embrace self assessment system. The effectiveness of the implementation of the inspection results of the calculation of income tax and the individual income tax in particular the realization of Inspection Warrant (SP2) Tax on KPP Pratama Manado, in terms of the settlement are calculated based on the issuance and realization (SP2) Tax is completed, which have a higher effectiveness 2010-2012 the same is included in the criteria effectively with a percentage of 100% and the results of the calculation in terms of the effectiveness of the completion of the acceptance of the results of the examination are calculated based on the target and the realization SP2 Tax, which had a degree of effectiveness in 2010 (101.8%), in 2011 (103, 4%), and 2012 (113.1%) of which were included in the criteria is very effective. That means that the performance of the KPP Pratama Manado is very good because it can meet the set targets, and the KPP Pratama ManadoÂ  should be able to continue to defend it.